In vitro and in vivo antitrypanosomal activities of selected medicinal plants - Othman, Dyary Hiewa (2013)
Surra, a hemoprotozoan disease caused by Trypanosoma evansi, is considered endemic to livestock in Peninsular Malaysia and currently the very few drugs available for treatment of the disease are old, toxic or ineffective. This study was conducted to evaluate the potential antitrypanosomal activities of the aqueous and ethanolic extracts of seeds of Nigella sativa and bulbs of Allium sativum, as well as the aqueous and ethanolic extracts of leaves of 11 medicinal plants, namely Acanthus ilicifolius, Aquilaria malaccensis, Cordyline terminalis, Derris elliptica, Garcinia hombroniana, Goniothalamus tapis, Goniothalamus umbrosus, Maesa ramentacea, Pereskia grandifolia, Plumeria rubra, and Strobilanthes crispus. The potency of each plant extract against T. evansi strain Te7 was screened through the determination of the median inhibitory concentration (IC50) on trypanosomes cultures in 24-well microtiter plates. The results of the study showed that the IC50 for G. umbrosus ethanolic extract was 2.30 ± 0.90 μg/mL and for S. crispus aqueous extract it was 800.97 ± 278.33 μg/mL. In vitro cytotoxicity assay was performed to determine the median cytotoxic concentration (CC50) of the extracts. The MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) cell proliferation assay was conducted and the results showed variable toxicity levels of the extracts towards the mammalian cell lines, Vero cells. Median cytotoxic concentration of G. umbrosus ethanolic extract on Vero cells was 29.10 ± 7.36 μg/mL and 14533.87 ± 296.86 μg/mL for G. hombroniana aqueous extract. The selectivity index (SI) was calculated from CC50 and IC50. For the G. hombroniana, A. malaccensis, and C. terminalis aqueous extracts, the SI values were 616.36, 47.38, and 27.17, respectively. The mode of action of G. hombroniana aqueous extract in vitro was elucidated by culturing T. evansi with the extract for 24 hours followed by staining the trypanosomes with the DNA-binding fluorescent stain bisbenzimide H33258. The results of the study showed that the extract might act via inhibition of kinetoplast division during mitosis of T. evansi. Acute toxicological effects of G. hombroniana aqueous extract, at concentrations of 300, 2000 and 5000 mg/kg body weight, were investigated through the oral acute toxic class (ATC) method on 24 female Sprague-Dawley rats. No significant difference in body weight or food and water consumption (p>0.05) was observed among groups of experimental rats. The hematological parameters were determined in the G. hombroniana aqueous extract-treated rats, which included erythrocyte, leukocyte and thrombocyte counts, hemoglobin concentration, packed cells volume, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and plasma proteins, and did not show significant differences (p>0.05) among groups. The serum biochemical parameters including albumin,alanine transaminase (ALT), aspartate transaminase (AST), total bilirubin, cholesterol, creatinine, γ-glutamyl transferase (GGT), glucose, urea, total protein, and lactate dehydrogenase (LDH) did not reveal significant differences (p>0.05) among the groups. The histopathological changes in the liver, spleen, kidneys, and heart were not significant (p>0.05) between control and treated groups, except for the rats given 5000 mg/kg body weight of the extract. In the later rats, there was slight congestion of the liver and kidneys, narrowing of the liver sinusoids and an increase in the number of Kupffer cells around the portal areas. The median lethal dose (LD50) of the extract was higher than 5000 mg/kg body weight, which is beyond the limit permitted to be used for testing in rats. Phytochemical screening of G. hombroniana aqueous extract revealed the presence of flavonoids, phenols, tannins, and saponins. The aqueous extract of G. hombroniana was tested on experimentally T. evansi-infected rats. The results of the test showed that the post-infection survival time in the untreated control group was 6.60 ± 0.24 days, while in the groups treated with 600 and 1200 mg/kg body weight G. hombroniana it was 12.80 ± 0.20 and 12.80 ± 0.37 days, respectively, which was significantly (p<0.05) longer than that observed in the untreated control group of rats. These findings suggest that the G. hombroniana aqueous extract has potential and is effective in the treatment of trypanosomiasis. In summary, the study suggests that the possible mode of action of G. hombroniana aqueous extract in its antitrypanosomal activity is through inhibition of kinetoplast division during mitosis of T. evansi, the LD50 of G. hombroniana aqueous extract is higher than 5000 mg/kg body weight and the extract significantly extended the post-infection survival of rats experimentally infected with T. evansi.